RELATIONSHIP OF EATING PATTERN AND STRESS LEVELS WITH PRE ECLAMPSIA AMONG PREGNANT WOMEN AT CIKAMPEK HEALTH CENTRE IN 2021 - Pratiwi, Risky; Anni Suciawati; Rukmaini (Journal of Global Research in Public Health, 2022)
Preeclampsia is one of the complications in pregnancy that has criteria where gestational age is > 20 weeks, which is marked by swelling of the legs, and positive urine protein values ​​caused by various factors. Preliminary study results show that on average pregnant women with preeclampsia have unhealthy eating patterns and abnormal stress levels. This study aimed to determine the relationship between diet and stress levels with preeclampsia in pregnant women at the Cikampek Health Center in 2021. This study is a quantitative analytic study with a case control design. The sample in this study consisted of 96 people consisting of 48 samples of the preeclampsia group and 48 samples not experiencing preeclampsia with accidental sampling technique. Bivariate data analysis used Chi Square statistical test to determine the relationship between variables. Pregnant women with a healthy diet 53.1%, and stress levels with a mild category was 58.3%. Bivariate analysis revealed that there was a relationship between diet (p = 0.000) and stress levels (p = 0.004) with preeclampsia in pregnant women at the Cikampek Health Center in 2021. There was a significant relationship between diet and stress levels with preeclampsia in pregnant women at the Cikampek Health Centre in 2021 with a p-value <0.05. It is hoped that in carrying out the antenatal care service program, they can immediately carry out the making of a counseling schedule on how to calculate the nutrients consumed by the mother and the right amount of nutritional needs when pregnant women and stress management for pregnant women as an effort to prevent the occurrence of preeclampsia.